Technological Properties of Cylinder Liners of Automotive Internal Combustion Engines Restored by Centrifugal Induction Sintering - Ilyamov, Khasan; Zhumagulov, Zhandos; Sarkynov, Erbol; Abdreshov, Shamil; Bakyt, Gabit; Saparbayev, Yerzhigit (Communications - Scientific Letters of the University of Zilina, 2024)
Cylinder liners of an automotive internal combustion engine are subject to significant losses during operation. Severe operating conditions of cylinder liners lead to the appearance of various defects that must be eliminated to ensure the performance of the internal combustion engine. Currently, several methods have been developed for restoring and strengthening the inner surface of cylinder liners of automobile and tractor engines. Analyzing the considered methods for strengthening and restoring cylinder liners, their advantages and disadvantages from the point of view of increasing their durability, it can be assumed that the high-quality restoration of cylinder liners will be provided by a method of applying a coating by centrifugal induction sintering of powder material. Self-fluxing powders were used as baked powder material.
Keywords: sleeve cylinder; NI-resist inserts; tinned and chrome rings; micro-contact setting; metal contacting; centrifugal induction sintering cylinder -piston group